Antibacterial Property of Hanguana Malayana (Bakong) Crude Leaf Ethanolic Extract against Staphylococcus Aureus - Vandon T. Borela; Jan Arianne B. Urbano; Andrei Joshua A. Tayag; Myco G. Teresa (Journal La Lifesci, 2020)
Hanguana Malayana, known as Bakong plant is an invasive macrophytic plant found in few regions of the Philippines. Due to its mode of propagation, it occupies large spaces and it invades the space that’s allotted for the crops of local farmers. Hence, the researchers investigate this plant for beneficial uses. In this study, the effect of the different concentrations of H. malayana crude ethanolic leaf extract on S.aureus is evaluated on the basis of the study stating that the plant is a potential resources of bioactive phytoconstituents. The bioactive compounds shows synergistic impact that made it have an compelling antibacterial property against Staphylococcus aureus. In this think about, it was as it were demonstrated to have antibacterial property against gram-positive microbes, Staphylococcus aureus. This research concluded that the Hanguana malayana crude leaf ethanolic extract has an antibacterial property against Staphylococcus aureus.